Costumes and costume designers of Theatro da Paz Opera Festival in Belém (PA): preliminary studies (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2023)
The purpose of this study is to formulate an historical overview about the development of opera performances in the capital of the Brazilian state, Pará. Besides, the paper speculates on the role of this gender to the city of  Belém. This preliminar work is the backgroung to deepen the main study: an analysis of the presence and protagonism of local technical artists, specially costume designers, in the productions of the Theatro da Paz Opera Festival. The argument is based on the analysis of different contemporary political point of views towards the cultural administration of the State and, mainly, with the opera.
Keywords: Opera festival; opera; Belém; Amazon; costume design; Theatro da Paz